2016
DOI: 10.7476/9788575114551
|View full text |Cite
|
Sign up to set email alerts
|

Work in Brazil: essays in historical and economic sociology

Abstract: Todo o conteúdo deste trabalho, exceto quando houver ressalva, é publicado sob a licença Creative Commons Atribição 4.0.Todo el contenido de esta obra, excepto donde se indique lo contrario, está bajo licencia de la licencia Creative Commons Reconocimento 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…El proceso keynesiano no presenta un asentamiento similar al europeo, siendo, la segunda mitad del siglo XX, un periodo recorrido por economías de naturaleza más inestable y subsidiaria de occidente (Ramos et al, 2015). Los marcos políticos de la mayoría de los países latinoamericanos navegan entre la inestabilidad y los conflictos durante este periodo, impactando en trayectorias laborales marcadas por una profunda desigualdad social y una estructura de derechos laborales menos definida (Cardoso, 2016). El periodo de crisis de deuda que el continente experimenta en los años 1980, sin embargo, también abre la puerta al neoliberalismo en el continente (Limonad, 2021).…”
Section: Conclusiónunclassified
“…El proceso keynesiano no presenta un asentamiento similar al europeo, siendo, la segunda mitad del siglo XX, un periodo recorrido por economías de naturaleza más inestable y subsidiaria de occidente (Ramos et al, 2015). Los marcos políticos de la mayoría de los países latinoamericanos navegan entre la inestabilidad y los conflictos durante este periodo, impactando en trayectorias laborales marcadas por una profunda desigualdad social y una estructura de derechos laborales menos definida (Cardoso, 2016). El periodo de crisis de deuda que el continente experimenta en los años 1980, sin embargo, también abre la puerta al neoliberalismo en el continente (Limonad, 2021).…”
Section: Conclusiónunclassified
“…These data require an interpretation of the recent labour history of both territories. Both the Spanish and Brazilian cases go through authoritarian periods in the second half of the twentieth century, which implies that the construction of their social and labour protection models are late and fragile [7,89]. In the Spanish case, this aterialized in the duality of labour at the turn of the millennium.…”
Section: Study 2: Cross-national Comparison: Brazil and Spainmentioning
confidence: 99%
“…This implies a stronger economy than in Brazil, with a social protection system that provides more guarantees for employees. In the Brazilian case, there is a tendency towards economic subsidiarity with European countries and North America, which, together with the prior fragility of employment, places the Brazilian labour context in a situation of poorer protection [7]. Against this background, the scientific literature has shown that job insecurity is a phenomenon mediated by conditions of poverty and resource availability [15,91].…”
Section: Study 2: Cross-national Comparison: Brazil and Spainmentioning
confidence: 99%
See 1 more Smart Citation